Mediolateral force distribution at the knee joint shifts across activities and is driven by tibiofemoral alignment. (June 2017) - Kutzner, I.; Bender, A.; Dymke, J.; Duda, G.; von Roth, P.; Bergmann, G.
Abstract : Aims: Tibiofemoral alignment is important to determine the rate of progression of osteoarthritis and implant survival after total knee arthroplasty (TKA). Normally, surgeons aim for neutral tibiofemoral alignment following TKA, but this has been questioned in recent years. The aim of this study was to evaluate whether varus or valgus alignment indeed leads to increased medial or lateral tibiofemoral forces during static and dynamic weight-bearing activities. Patients and Methods: Tibiofemoral contact forces and moments were measured in nine patients with instrumented knee implants. Medial force ratios were analysed during nine daily activities, including activities with single-limb support (e.g. walking) and double-limb support (e.g. knee bend). Hip-knee-ankle angles in the frontal plane were analysed using full-leg coronal radiographs. Results: The medial force ratio strongly correlated with the tibiofemoral alignment in the static condition of one-legged stance (R² = 0.88) and dynamic single-limb loading (R² = 0.59) with varus malalignment leading to increased medial force ratios of up to 88%. In contrast, the correlation between leg alignment and magnitude of medial compartment force was much less pronounced. A lateral shift of force occurred during activities with double-limb support and higher knee flexion angles. Conclusion: The medial force ratio depends on both the tibiofemoral alignment and the nature of the activity involved. It cannot be generalised to a single value. Higher medial ratios during single-limb loading are associated with varus malalignment in TKA. The current trend towards a 'constitutional varus' after joint replacement, in terms of overall tibiofemoral alignment, should be considered carefully with respect to the increased medial force ratio. Cite this article: Bone Joint J 2017;99-B:779–87.